The Online Help-Seeking Behaviors of Middle Adolescent Students with Migrant Mothers - Kyzzell Nichole Z. Poserio; Rhoda Joy A. Avila (Philippine Social Science Journal, 2024)
The relevance of accessing care and support has been found to be valuable in sustaining well-being among adolescents. However, only a few studies have been conducted to understand the online help-seeking behaviors of middle adolescent students whose mothers work abroad. Thus, the study aimed to uncover the nature of online help-seeking behaviors and explore the facilitators and barriers to these behaviors. Ten (10) middle adolescent students were interviewed, and their experiences revealed several key themes using the phenomenological method. The findings revealed that the online help-seeking behaviors of left-behind adolescents include the availability of a helper, reaching out, self-reliance, and coping strategies. Additionally, facilitating factors include convenience and safe space, and hindering factors consist of the unavailability of helpers and negative perceptions toward help sources. The results highlighted the importance of leveraging informal support networks, seeking professional help, and maintaining communication with migrant mothers among middle adolescents.